The minority game: A statistical physics perspective - Sherrington, D (2006)
A brief review is given of the minority game, an idealized model stimulated by a market of speculative agents, and its complex many-body behaviour. Particular consideration is given to analytic results for the model rather than discussions of its relevance in real-world situations. (c) 2006 Elsevier B.V. All rights reserved.